Explorando a probabilidade no ensino médio: uma sequência didática utilizando um jogo - Santos, Tania Maria dos (2023)
Probability is a branch of mathematics that plays a significant role in our daily lives and is fundamental in several areas of knowledge. It is recognized that an adequate introduction to this content from the early years of elementary school is essential, as an inadequate approach can result in difficulties in the student’s educational trajectory. In order to assess students’ understanding from previous years, we chose to apply a diagnostic assessment to guide our approach to this content in high school, identifying the areas of greatest challenge. Subsequently, we adopted a playful strategy in which all students participate in the activity and we use a game to introduce the concept of probability in high school. This made learning more engaging and gave meaning to the students’ learning experience. Finally, we apply a final assessment to measure the effectiveness of this strategy and verify its impact on students’ understanding. This assessment provided concrete data on student progress, serving as a valuable indicator for the continuous improvement of our pedagogical approach.